Microsoft Office PowerPoint 2007 : top 100 simplified tips & tricks - McFedries, Paul (Top 100 simplified tips & tricks., 2007)
Clear instructions for tasks that reveal secrets and timesaving tricks to make you more productive with PowerPoint 2007.